2010
DOI: 10.1007/s11120-009-9516-1
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, phylogeny, and ecology of the heliobacteria

Abstract: Heliobacteria are a recently discovered group of anoxygenic phototrophic bacteria, first described in 1983. Heliobacteria contain bacteriochlorophyll g, a pigment unique to species of this group, and synthesize the simplest photosynthetic complexes of all known phototrophs. Also, unlike all other phototrophs, heliobacteria lack a mechanism for autotrophy and produce endospores. Four genera of heliobacteria containing a total of 10 species are known. Species of the genera Heliobacterium, Heliobacillus, and Heli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…All of the cultured heliobacteria require organic carbon for anoxygenic growth, and several of the species can fix nitrogen (1,2). Heliobacteria are the only cultured Gram-positive photosynthetic bacteria and are phylogenetically related to the bacterial phylum Firmicutes, such as the aerobic Bacillus and anaerobic Clostridia (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All of the cultured heliobacteria require organic carbon for anoxygenic growth, and several of the species can fix nitrogen (1,2). Heliobacteria are the only cultured Gram-positive photosynthetic bacteria and are phylogenetically related to the bacterial phylum Firmicutes, such as the aerobic Bacillus and anaerobic Clostridia (1).…”
mentioning
confidence: 99%
“…Heliobacteria are the only cultured Gram-positive photosynthetic bacteria and are phylogenetically related to the bacterial phylum Firmicutes, such as the aerobic Bacillus and anaerobic Clostridia (1). Among 10 cultured heliobacteria (2), Heliobacterium modesticaldum is the only one that can grow at temperatures of Ͼ50°C. Madigan and co-workers (1,3) reported that pyruvate, lactate, acetate (ϩHCO 3 Ϫ ), or yeast extract can support the phototrophic growth of H. modesticaldum, and our recent studies demonstrated that D-sugars can also support the growth of H. modesticaldum (4).…”
mentioning
confidence: 99%
“…The GSB use the reverse tricarboxylic acid cycle, and many of the FAPs use the 3-hydroxypropionate cycle (Zarzycki et al, 2009). The Gram-positive heliobacteria lack any known autotrophic carbon fixation pathway and usually grow photoheterotrophically (Asao and Madigan, 2010). Similarly, the aerobic anoxygenic phototrophs, which are closely related to the purple bacteria, lack any apparent ability to fix inorganic carbon.…”
Section: Carbon Fixation Pathwaysmentioning
confidence: 99%
“…The previous examination of several other Heliobacteria species for sporulating genes has indicated that sporulation gene presence may be universal within the heliobacteria (KimbleLong & Madigan, 2001). It should be noted that a set of genes involved in bacteriochlorophyll (Bchl) g biosynthesis, not found in other phototrophs, were frequently reported in other heliobacteria species (reviewed in Asao & Madigan, 2010). These enzymes were not clustered into the core-genome due to their absence in the non-phototrophic Firmicutes.…”
Section: Heliobacteria (Firmictues)mentioning
confidence: 99%